Analysis of Advertising Effectiveness Free Shipping and Consumer Trust to Increase Purchase Decisions - Putri Hawa Alkatiri; Asep Muhamad Ramdan; Faizal Mulia Z (Almana : Jurnal Manajemen dan Bisnis, 2022)
Purchase decisions are an important part of marketing, to support consumer purchase decisions it is necessary to have the effectiveness of advertising and consumer trust so that consumer purchase decisions do not become doubtful. This study aims to determine the effect of Advertising Effectiveness Free Shipping and Consumer Trust on purchase decisions. In this study, the emergence of problems in the purchasing decision variables on the time dimension of purchase is because those who use the Shopee online shopping application are not comparable to those who make purchases. This research method uses quantitative methods with an associative method approach. The sampling technique in this study used probability sampling, namely Simple Random Sampling, the samples taken in this study were 270 users of the Shopee online shopping application in Sukabumi City. The data analysis technique used in this research is multiple correlation coefficient, coefficient of determination test, simultaneous test (f test), multiple linear regression, and partial test (t-test). The results showed that there was a positive and significant influence of the Advertising Effectiveness of Free Shipping on the purchase decision variables and a positive and significant influence of the consumer trust variable on the purchase decision variables.